Group Riding in Western Australia: An Examination of Crashes, Outcomes and Behaviour - Fraser, Michelle Louise (Curtin University, 2019)
This study aimed to gain an understanding of the safety issues affecting group riders in Perth, Western Australia. Phase 1 consisted of an in-depth longitudinal study of cyclists hospitalised in an on-road crash. Phase 2 involved a naturalistic study of unsafe events and traffic violations observed among group riders. The findings suggest that interventions targeting the road environment, group rider training and motorist education have the potential to improve safety for group riders.